2015
DOI: 10.1371/journal.pone.0128308
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor 4A1 (NR4A1) as a Drug Target for Renal Cell Adenocarcinoma

Abstract: The orphan nuclear receptor NR4A1 exhibits pro-oncogenic activity in cancer cell lines. NR4A1 activates mTOR signaling, regulates genes such as thioredoxin domain containing 5 and isocitrate dehydrogenase 1 that maintain low oxidative stress, and coactivates specificity protein 1 (Sp1)-regulated pro-survival and growth promoting genes. Transfection of renal cell carcinoma (RCC) ACHN and 786-O cells with oligonucleotides that target NR4A1 results in a 40–60% decrease in cell proliferation and induction of apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 41 publications
8
80
0
Order By: Relevance
“…Similar results were observed after treatment with DIM-C-pPhCO 2 Me. We also recently observed similar results in a p53-mutant renal adenocarcinoma cell line (Hedrick et al 2015) which showed that induction of SESN2 was ROS-dependent. This was consistent with previous reports showing that SESN2 was an oxygen-sensing gene (Budanov et al 2002).…”
Section: Sinr4a1 and Dim-c-pphco 2 Me Inhibit Mtor Signalingsupporting
confidence: 76%
“…Similar results were observed after treatment with DIM-C-pPhCO 2 Me. We also recently observed similar results in a p53-mutant renal adenocarcinoma cell line (Hedrick et al 2015) which showed that induction of SESN2 was ROS-dependent. This was consistent with previous reports showing that SESN2 was an oxygen-sensing gene (Budanov et al 2002).…”
Section: Sinr4a1 and Dim-c-pphco 2 Me Inhibit Mtor Signalingsupporting
confidence: 76%
“…The cells were visualized by microscopy (Advanced Microscopy), and NR4A1 localization was determined by green fluorescence. DAPI was used to stain the nucleus, and images were taken sequentially of NR4A1, DAPI, and then merged (28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%
“…SKBR3, MDA-MB-231, and MCF-7 cancer cells (3.0 ϫ 10 5 per well) were seeded in Dulbecco's modified Eagle's medium-Ham's F-12 medium supplemented with 2.5% charcoalstripped fetal bovine serum and were allowed to attach for 24 h. The cells were transfected with 100 nM si␤1-integrin, siNR4A1, siSp1, or sip300 for 72 h or treated with various C-DIM compounds. Cell lysates were analyzed by Western blotting as described previously (28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, some selected compounds in the series of DIM analogs, such as DIM-C-pPhO, DIM-C-pPhOH and DIM-CpPhCO 2 Me, act as NGFI-B antagonists. These compounds can induce apoptosis and inhibit tumor growth of cancers, such as pancreatic [84], lung [85], colon [86], breast cancer cells [81] and renal cell adenocarcinoma [87], where NGFI-B is overexpressed, via targeting and suppression of NGFI-B-mediated pro-oncogenic pathways. NGFI-B is shown to promote breast cancer invasion and metastasis by activating TGF-β/SMAD signaling [88] and NGFI-B antagonists can significantly suppress TGF-β-induced migration of breast cancer cells [89].…”
Section: Ngfi-bsmentioning
confidence: 99%